Evaluation of Students' Interest, Attitudes, and Science Process Skills in Science Subjects - Ernawati, Margaret Dwi Wiwik; Asrial, Asrial; Perdana, Rahmat; Septi, Sabila Eka; Rohana, Siti; Nawahdani, Ahmad Mansur (Journal of Education Reseach and Evaluation, 2022)
The main problem in learning science is shaping students' interests, attitudes and science process skills. This study aims to analyze the comparison and relationship of interests, attitudes and science process skills in science learning in two schools. This research method is quantitative with comparative type. The number of respondents as a sample is 140 students. The data collection technique used purposive sampling. The results of the study using the t-test that there are significant differences in the indicators of interest, attitude and science process skills of students. The results of the correlation test between interests, attitudes and science process skills in students showed that interests, attitudes and science process skills were interrelated. The limitation of this study is that it only uses two indicators per variable. Where it is better to use several indicators to find out in more detail the influence of the variables of interest, attitude, and science process skills on students. The researcher recommends further research to vary more indicators used in order to find out in more detail the variables studied and the researcher recommends conducting research at the junior high school level.